Chemical and Pharmacological Investigation of the Stem Bark of Synadenium grantii - Munhoz, Antonio C. M.; Minozzo, Bruno R.; Cruz, Luiza S.; Oliveira, Thaís L.; Machado, Willian M.; Pereira, Airton V.; Fernandes, Daniel; Manente, Francine A.; Vellosa, José C. R.; Nepel, Angelita; Barison, Andersson; Beltrame, Flávio L. (Planta Medica, 2014)
Based on the fact that Synadenium grantii is used in folk medicine for the treatment of peptic ulcers and inflammatory diseases, this work describes its chemical and pharmacological properties. Pharmacological investigation of the crude bark extract showed a high antioxidant activity over several scavenger systems, such as 2,2′-azino-bis (3-ethylenebenzothiazoline-6-sulfonic acid)• +, 1-diphenyl-2-picrylhydrazyl•, O2• −, and HOCl, as well as an enzymatic system with human myeloperoxidase and an ex vivo hemolysis system. Furthermore, the oral administration of the crude bark extract was able to reduce carrageenan-induced rat paw edema as effectively as ibuprofen. These biological activities may be associated with the presence of flavonoids and terpenes, as revealed by HPLC and NMR analyses of the crude stem bark extract. The phytochemical investigations in this study resulted in the isolation of friedelin and 3β-friedelinol for the first time, while euphol and lanosterol were also isolated.
Keywords: Synadenium grantii; Euphorbiaceae; antioxidant activity; anti-inflammatory activity; flavonoids; terpenes